INOVASI PRODUK GADUNG SEBAGAI UPAYA PENINGKATAN EKONOMI MASYARAKAT MELALUI PERAN KKN TEMATIK POSDAYA BERBASIS MASJID DESA BALAK KECAMATAN SONGGON - Anis Fauzi; Endhang Suhilmiati (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2019)
The implementation of this service program is based on preliminary observations showing that the level of business results of the gadung owned by the community is considered low, lacking the attractiveness of the consumers and even looks not worth the cost and energy spent. Mosque-Based KKN Thematic Posdaya Baitul Mukarromah Derwono Hamlet, Balak village, Songgon Subdistrict, developed several programs aimed at improving the quality of community businesses. This program is running well, including guidance, mentoring and training in processing gadung tubers into chips and training to innovate making processed variants of gadung chips for the public in general. This program will be continued by the community to help improve one's own economy.